2013
DOI: 10.1063/1.4824993
|View full text |Cite
|
Sign up to set email alerts
|

Epileptogenic focus detection in intracranial EEG based on delay permutation entropy

Abstract: Epileptogenic localization is a critical factor for successful epilepsy surgery. Determining the epileptogenic hippocampus with single channel intracranial electroencephalography (iEEG) recording is beneficial to decrease the risk of infection compared with that based on multi-channel iEEGs. Delay permutation entropy (DPE) methodology is presented in this study to measure iEEG with different delay lag based on focal epileptogenic zone. A total of 1600 20-s epileptic iEEG are evaluated and are used as features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 12 publications
2
45
0
Order By: Relevance
“…The highest value of the MCC parameter for the Morlet wavelet kernel confirms the suitability of the Morlet wavelet kernel for the classification of the focal and non-focal EEG signals. The comparison of our proposed method with previously reported methods [65,66] using the same database is presented in Table 4. Our proposed method shows the highest classification accuracy of 87%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The highest value of the MCC parameter for the Morlet wavelet kernel confirms the suitability of the Morlet wavelet kernel for the classification of the focal and non-focal EEG signals. The comparison of our proposed method with previously reported methods [65,66] using the same database is presented in Table 4. Our proposed method shows the highest classification accuracy of 87%.…”
Section: Resultsmentioning
confidence: 99%
“…In [65], delay permutation entropy (DPE) is used as the feature for the classification of focal and non-focal EEG signals. The maximum classification accuracy obtained using the SVM classifier for 50 focal and 50 non-focal EEG signals is 84%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ouyang et al [9] investigated by multiscale PE the transition of brain activities towards an absence seizure. Zhu et al [10] demonstrated, by experimental results, that PE is able to identify epileptic seizures in EEG and intracranial EEG (iEEG). The same authors proposed an unsupervised multi-scale K-means (MSK-means) algorithm to distinguish epileptic EEG signals and to identify epileptic zones [11].…”
Section: Introductionmentioning
confidence: 99%
“…EEGs which record the voltage fluctuations resulting from ionic current flows within the neurons are capable of increasing insights into brain dysfunction and even of yielding information useful for diagnostic purposes [2]. Nowadays, it is widely used in the detection of epilepsy [3], [4] as well as characterization of sleep phenomena [5], encephalopathy [6] or Creutzfeldt-Jakob disease [7] and monitoring the depth of anesthesia [8] and the location of epileptic focus [9]. Automatic epileptic classification systems are the trend in both research and clinical areas because the traditional visual inspection of EEG signals requires highly trained medical professionals.…”
Section: Introductionmentioning
confidence: 99%